Women's Social Network in The Worker Union of PT. Tirta Mahakam Resources Tbk: Jaringan Sosial Buruh Perempuan di Dalam Serikat Buruh Pada Perusahaan PT. Tirta Mahakam Resources Tbk - Novitasari, Novitasari; Hakim, Aji Qamara (Progress In Social Development, 2020)
ABSTRACT: This study aims to analyze the social networks of women workers in the KASBI Labor Union. The union was founded in 2005 to fight for women workers who work in the PT. Tirta Mahakam Resources Tbk. In a factory that is predominantly women, the need for a union is a must as a means of protection. For this reason, the existence of the Union is very dependent on the struggle of women in it. From the observations, it can be identified that six actors are the centers of information for women labor union members. Divided into categories of stars (Star) and opinion leaders (Opinion Leader) and recruitment. From the observations, six actors have the most extensive social networks among other individuals. The six actors also have different interaction models, this is a potential asset for both the actor and the Union. There are three networks in it, namely interest networking (interests), sentiment networking (emotional network), and power networking (power network). The typology of social capital of the Union is also to bridge the bridging of social capital, which is that it leads to the search for joint answers to solve problems faced by the group and is open to other unions. ABSTRAK: Penelitian ini bertujuan menganalisis jaringan sosial buruh perempuan di dalam Serikat Buruh KASBI. Serikat yang berdiri pada tahun 2005 dalam upaya perjuangan buruh perempuan yang bekerja di dalam pabrik PT. Tirta Mahakam Resources Tbk. didalam pabrik yang mayoritas perempuan, Kebutuhan akan adanya Serikat merupakan keharusan sebagai sebuah wadah perlindungan. Untuk itu eksistensi Serikat sangat tergantung pada perjuangan perempuan di dalamnya. Dari hasil pengamatan dapat diidentifikasi terdapat enam aktor yang menjadi pusat informasi bagi anggota Serikat Buruh perempuan. Terbagi menjadi kategori bintang (Star) dan pemimpin opini (Opinion Leader) dan rekrutmen. Dari hasil pengamatan, terdapat enam aktor memiliki jaringan sosial yang paling luas diantara indivisu-individu lainya. Keenam aktor juga memiliki model interaksi yang berbeda-beda, hal tersebut merupkan modal yang potensial bagi aktor maupun Serikat. Terdapat tiga jaringan di dalamnya yaitu jaringan interest networking (kepentingan), sentiment networking (jaringan emosi), dan power networking (jaringan kekuasaan). Tipologi modal sosial Serikatpun bersifat menjembatani bridging social capital yaitu yang mengarah kepada pencarian jawaban bersama untuk menyelesaikan masalah yang dihadapi oleh kelompok serta terbuka kepada Serikat lain.